Psychological Antecedents of Promotive and Prohibitive Voice: A Two-Wave Examination - Liang, Jian; Farh, Crystal I. C.; Farh, Jiing-Lih (Academy of Management Journal, 2012)
The present study demonstrates how three psychological antecedents (psychological safety, felt obligation for constructive change, and organization-based self-esteem) uniquely, differentially, and interactively predict supervisory reports of promotive and prohibitive “voice” behavior. Using a two-wave panel design, we collected data from a sample of 239 employees to examine the hypothesized relationships. Our results showed that felt obligation was most strongly related to subsequent promotive voice; psychological safety was most strongly related to subsequent prohibitive voice; and organization-based self-esteem was reciprocally related to promotive voice. Further, although felt obligation strengthened the positive effect of psychological safety on both forms of voice, organization-based self-esteem weakened this effect for promotive voice. Theoretical and practical implications are discussed.